Compost Tips for the Home Gardener - Sydney Park Brown (EDIS)
ENH 1065, a 3-page fact sheet by Sydney Park Brown, discusses what compost is, why to do it, what can be composted, building and managing a compost pile, how to use it, and troubleshooting. Includes references. Published by the UF Department of Environmental Horticulture, August 2007.